Inovasi Metode Pembelajaran Pendidikan Agama Islam dalam Meningkatkan Prestasi Belajar Siswa - Isnawardatul Bararah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Islamic religious education in schools or madrasas, in its implementation, still shows problems that are less than encouraging. So far, there is an impression that students are less enthusiastic in participating in PAI learning. The teacher becomes the center of attention of students and seems to be the sole source of information. This fact gets worse when the available reference books are not proportional to the number of students. So that the learning process is dominated by note-taking activities. In the end, the teacher failed to create a dialogical atmosphere in classroom learning. Therefore, innovation of learning methods in education is very necessary. Innovation is a manifestation of a change that is not just changing for the better, innovation in learning methods is a systematic and structured update step from various aspects. With innovation, everything will be renewed for a better purpose. Teachers who innovate in learning methods are able to open up the horizons of innovative students, so that student enthusiasm emerges which then instills facts or concepts into students' deepest memories. Through innovative learning methods, the classroom atmosphere is not confined to a rigid and monotonous atmosphere. Students need to be invited more to discuss, interact, and have dialogue so that they are able to construct scientific concepts and principles themselves, not by being fed or lectured. Students also need to be accustomed to differing opinions so that they become intelligent and critical figures. Of course, democratically, without forgetting scientific principles, the teacher needs to provide reinforcements so that there are no misunderstandings.